Supreme Court Decision Number 34P/HUM/2022 and Efforts to Strengthen the Prevention and Handling of Sexual Violence in Higher Education Institutions - Susi Dian Rahayu; Arifudin; Winarsih (Universitas Negeri Semarang, 2026)
In response to the increasing prevalence of sexual violence cases in higher education institutions, the Ministry of Education, Culture, Research, and Higher Education issued Ministerial Regulation No. 30 of 2021 on the Prevention and Handling of Sexual Violence in Higher Education Institutions. However, the regulation has sparked debate among the public, particularly regarding Article 5 (paragraph 2), which contains the phrase “without consent” a phrase deemed open to multiple interpretations, legalizing adultery, and contradicting societal norms and religious values. This controversy subsequently became the subject of a petition for judicial review at the Supreme Court in Case No. 34 P/HUM/2022, by the Minangkabau Traditional Council (LKAAM) of West Sumatra. However, in its ruling through Supreme Court Decision No. 34 P/HUM/2022, the Supreme Court dismissed the petition. This study examines about Supreme Court Decision Number 34/P/HUM/2022 and efforts to strengthen legal protection for the prevention and handling of sexual violence in higher education institutions. The theory used in this study is the Theory of Legal Protection by Philipus Hadjon. The research findings that, in relation to the prevention and handling of sexual violence in higher education institutions, the presence of Ministry of Education, Culture, Research, and Technology Regulation Number 30 of 2021, reinforced by Supreme Court Decision Number 34 P/HUM/2022, provides both preventive and repressive legal protection.